Terhelti védekezések jogi és pszichológiai szempontú értékelése az adminisztratív csődbüntett köréből - Elek, Balázs; Hajdú, Krisztina (Debreceni Jogi Műhely, 2006)
Psychology plays a main role in the criminal procedure, in which the people’s personality is very important to be investigated and known. The psychological methods started being used only in the 19th century. During the legal proceedings the authorities must deal with people. The behavior of the people is very different. The authorities must know the basic rules of the psychology to understand these different behaviors of accused people. The human memory has a lot of regularity. The knowledge of these regularities make easier the efforts of the authorities to get the truth. In the whole process of the investigation the most important fact to know is the personality of the person who committed the crime. When the suspected is being heard, different type of personalities can cause different final resumes. Therefore the importance of the psychological knowledge in the legal occupation is unquestionable.